1984
DOI: 10.1507/endocrj1954.31.435
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of peripheral tissues and pituitary to thyroid hormone.

Abstract: We describe a 29-year-old male with thyroid hormone resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…
ANALYSIS of case reports of generalized resistance to thyroid hormone (TH) revealed that the affected subjects frequently had a delayed bone maturation or anomalies of bone structure including stippled epiphyses and short metacarpals [1,2]. It was also recognized that 15% of subjects had a height below the fifth percentile and 8% belos the third percentile [3].
…”
mentioning
confidence: 99%
“…
ANALYSIS of case reports of generalized resistance to thyroid hormone (TH) revealed that the affected subjects frequently had a delayed bone maturation or anomalies of bone structure including stippled epiphyses and short metacarpals [1,2]. It was also recognized that 15% of subjects had a height below the fifth percentile and 8% belos the third percentile [3].
…”
mentioning
confidence: 99%